2018
DOI: 10.1111/scs.12599
|View full text |Cite
|
Sign up to set email alerts
|

Living in a nursing home: a phenomenological study exploring residents’ loneliness and other feelings

Abstract: It is vital that healthcare professionals are aware of these feelings and pay much attention to resident preferences while developing (individualised) interventions to prevent loneliness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
74
3
14

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(94 citation statements)
references
References 29 publications
3
74
3
14
Order By: Relevance
“…Given the initial interruptions imposed by EL forced the older adults to accept, reflect and re-define as functions of changes along the EL trajectory. Similar to cancer patients, dying individuals and bereaved persons [46][47], acceptance of EL did not mean giving up or passivity for both ethnic groups in our study. It did require that these older adults openly recognized and confronted their limitations and the dark side of the human condition of being existential lonely.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Given the initial interruptions imposed by EL forced the older adults to accept, reflect and re-define as functions of changes along the EL trajectory. Similar to cancer patients, dying individuals and bereaved persons [46][47], acceptance of EL did not mean giving up or passivity for both ethnic groups in our study. It did require that these older adults openly recognized and confronted their limitations and the dark side of the human condition of being existential lonely.…”
Section: Discussionsupporting
confidence: 47%
“…In doing so, older adults tended to make sense and meaning of EL and were concerned with their overall well-being. Without this, the focus on "trapped" experience can leave the older adults question their meaning of life, as one counter to a normalization of "growing old" [47].…”
Section: Discussionmentioning
confidence: 99%
“…Feelings of loneliness leading to feelings of depression were common among residents in the present study (depression and/or anxiety was reported in 40.9% of the residents). The loss of care home residents’ self-determination due to institutionalisation was strongly related to loneliness and grief in a recent study [48]. Failure to find meaningful connections shows growing concerns about the critical rates of loneliness in residential care [49].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, there are two key limitations in the current understanding of EL. First, the idea that EL is a universal human experience was primarily based on studies of people from Western cultures [17,18]. It is unclear if people from Eastern cultures (e.g., Chinese) also experience EL.…”
Section: Introductionmentioning
confidence: 99%